Study the percentage of achievement attained by the mass of weight lifters of both sexes for the common weight categories of world champions - Mahdi, Mustafa Salih; Abdulhassan, Ghassan Adeeb (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to identify the difference in the quotient between male and female groups of similar weight groups according to the new amendment in the international weightlifting law for the categories of weight 55 and 81 kg in the percentage of achievement compared to the body mass of both sexes, while identifying some biomechanical variables such as height and deviations in addition to the total time To perform for both sexes, as well as to identify the causes of this difference between the two sexes, the world heroes who were photographed on the top three centers of the two categories 55 and 81 kg have been photographed. The research has come to know the percentages and the difference between males and females in addition to the reasons that lead to this difference were identified and the most important nature Body composition for both sexes anatomically and physiologically. The researcher recommended to continue studying the causes to reach broader scientific ranges.